A Test of the Tropical 200‐ to 300‐hPa Warming Rate in Climate Models. Issue 9 (21st September 2018) - McKitrick, Ross; Christy, John
Abstract: Overall climate sensitivity to CO2 doubling in a general circulation model results from a complex system of parameterizations in combination with the underlying model structure. We refer to this as the model's major hypothesis, and we assume it to be testable. We explain four criteria that a valid test should meet: measurability, specificity, independence, and uniqueness. We argue that temperature change in the tropical 200‐ to 300‐hPa layer meets these criteria. Comparing modeled to observed trends over the past 60 years using a persistence‐robust variance estimator shows that all models warm more rapidly than observations and in the majority of individual cases the discrepancy is statistically significant. We argue that this provides informative evidence against the major hypothesis in most current climate models. Key Points: Climate models embed countless minor hypotheses and at least one major, testable hypothesis related to equilibrium sensitivity We outline four criteria that identify a testable prediction of the major hypothesis, namely, tropical 200‐ to 300‐hPa warming CMIP5 models show a large, significant, and uniform warm bias in that layer of sufficient magnitude to reject the major hypothesis